PEDF and VEGF-A Output from Human Retinal Pigment Epithelial Cells Grown on Novel Microcarriers - Falk, Torsten (Hindawi Publishing Corporation, 2012)
Human retinal pigment epithelial (hRPE) cells have been tested as a cell-based therapy for Parkinson's disease but will require additional study before further clinical trials can be planned. We now show that the long-term survival and neurotrophic potential of hRPE cells can be enhanced by the use of FDA-approved plastic-based microcarriers compared to a gelatin-based microcarrier as used in failed clinical trials. The hRPE cells grown on these plastic-based microcarriers display several important characteristics of hRPE found in vivo: (1) characteristic morphological features, (2) accumulation of melanin pigment, and (3) high levels of production of the neurotrophic factors pigment epithelium-derived factor (PEDF) and vascular endothelial growth factor-A (VEGF-A). Growth of hRPE cells on plastic-based microcarriers led to sustained levels (>1 ng/ml) of PEDF and VEGF-A in conditioned media for two months. We also show that the expression of VEGF-A and PEDF is reciprocally regulated by activation of the GPR143 pathway. GPR143 is activated by L-DOPA (1 μM) which decreased VEGF-A secretion as opposed to the previously reported increase in PEDF secretion. The hRPE microcarriers are therefore novel candidate delivery systems for achieving long-term delivery of the neuroprotective factors PEDF and VEGF-A, which could have a value in neurodegenerative conditions such as Parkinson's disease.